Efficacy and safety of unilateral and bilateral percutaneous balloon kyphoplasty for AOspineA3/A4 osteoporotic thoracolumbar burst fractures. Issue 31 (31st July 2020) - Wan, Ruijie; Liu, Shaofan
Abstract : Abstract: To retrospectively evaluate the efficacy and safety of unilateral and bilateral percutaneous balloon kyphoplasty (PKP) in the treatment of osteoporotic thoracolumbar burst fractures. Retrospectively collected clinical data of 138 patients with osteoporotic thoracolumbar burst fractures who underwent unilateral (n = 70) and bilateral (n = 68) PKP in our hospital from March 2015 to December 2018. The general conditions, operation time, radiation exposure time, intraoperative blood loss, bone cement dosage, hospitalization expenses, and complications were collected from the two groups. Visual analog scale (VAS) values, Cobb's angle changes, average vertebral height changes, and Oswestry Dysfunction Index (ODI) values before treatment, 1 month, and 6 months after treatment were collected. There was no significant difference in gender (male: 28 vs 22; female 42 vs 46) and age (70.25 ± 7.10 vs 69.82 ± 8.20, P > .05) distribution between the two groups. The VAS score (7.38 ± 1.34 vs 2.52 ± 0.99, P < .05), ODI (77.24 ± 6.98 vs 23.11 ± 3.54, P < .05), vertebral mean height (16.71 ± 2.18 vs 17.05 ± 1.94, P < .05) and Cobb's angle (20.26 ± 3.21 vs 11.58 ± 3.20, P < .05) of the two groups were significantly improved after operation, but there was no significant difference between the two groups ( P > .05). There was no significant difference in the rate of cement leakage (10.29% vs 11.42%, P > .05), incision swelling (30.88% vs 19.71%, P > .05) and incidence of adjacent vertebrae (4.41% vs 5.71%, P > .05) between the two groups. Compared with bilateral PKP group, operation time (50.88 ± 7.38 vs 62.18 ± 8.01), intraoperative blood loss (14.54 ± 3.16 vs 22.03 ± 5.92), radiation exposure time (23.74 ± 3.41 vs 15.22 ± 3.70), bone cement dosage (4.36 ± 0.81 vs 5.16 ± 0.77) and hospitalization costs (2.38 ± 0.08 vs 2.74 ± 0.07) were significantly lower in the unilateral PKP group ( P < .05). Bilateral PKP and unilateral PKP have the same efficacy and safety in the treatment of osteoporotic thoracolumbar burst fractures. However, the unilateral PKP has the characteristics of short operation time, small trauma, low cost and short radiation exposure time, and has clinical application value.